Konsep Humanisme Dalai Lama XIV - Eusabius Ferceli So'o Kowe (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2022)
The Dalai Lama's humanism was born from his consciousness as an incarnation. In addition, he is also motivated to help other to be freed from their suffering. The key to the Dalai Lama's success is practice. Practices give rise to the Dalai Lama's understanding of human beings. For the Dalai Lama all who have feelings, experiences and sensations are equal. This view leads people to think about something else. The actions of one individual produce certain consequences. For humans need to develop compassion for other creatures. This attitude will lead to an attitude of universal responsibility. Life is sacred so that it cannot be abolished by certain individuals for any reason. Humans that one and the other live on the same earth to form a unity. The Dalai Lama discovered that humans are connected to one another because of love. It is this love relationship that allows for mutual care and dependence. Dependence on one another is natural. Education based on love from an early age will allow one person to grow up with mental health. Mental health is very important in supporting behavior. A mentally healthy person is one who involved in serving others and at least not harming others.